Crystal Structure of the Chloroplastic Oxoene Reductase ceQORH from Arabidopsis thaliana - Mas y mas, Sarah; Curien, Gilles; Giustini, Cécile; Rolland, Norbert; Ferrer, Jean-Luc; Cobessi, David (Frontiers in Plant Science, 2017)
Enzymatic and non-enzymatic peroxidation of polyunsaturated fatty acids give rise to accumulation of aldehydes, ketones, and α,β-unsaturated carbonyls of various lengths, known as oxylipins. Oxylipins with α,β-unsaturated carbonyls are reactive electrophile species and are toxic. Cells have evolved several mechanisms to scavenge reactive electrophile oxylipins and decrease their reactivity such as by coupling with glutathione, or by reduction using NAD(P)H-dependent reductases and dehydrogenases of various substrate specificities. Plant cell chloroplasts produce reactive electrophile oxylipins named -ketols downstream of enzymatic lipid peroxidation. The chloroplast envelope quinone oxidoreductase homologue (ceQORH) from Arabidopsis thaliana was previously shown to reduce the reactive double bond of -ketols. In marked difference with its cytosolic homologue alkenal reductase (AtAER) that displays a high activity toward the ketodiene 13-oxo-9(Z),11(E)-octadecadienoic acid (13-KODE) and the ketotriene 13-oxo-9(Z), 11(E), 15(Z)-octadecatrienoic acid (13-KOTE), ceQORH binds, but does not reduce, 13-KODE and 13-KOTE. Crystal structures of apo-ceQORH and ceQORH bound to 13-KOTE or to NADP+ and 13-KOTE have been solved showing a large ligand binding site, also observed in the structure of the cytosolic alkenal/one reductase. Positioning of the α,β-unsaturated carbonyl of 13-KOTE in ceQORH-NADP+-13-KOTE, far away from the NADP+ nicotinamide ring, provides a rational for the absence of activity with the ketodienes and ketotrienes. ceQORH is a monomeric enzyme in solution whereas other enzymes from the quinone oxidoreductase family are stable dimers and a structural explanation of this difference is proposed. A possible in vivo role of ketodienes and ketotrienes binding to ceQORH is also discussed.